The Urgency of English Learning in Elementary Schools to Prepare Students for Global Competence: A Literature Study (International Journal of Education and Literature, 2026)
Globalization and technological developments require students to have global competencies, one of which is English language skills. This study aims to examine the urgency of English learning in elementary schools (SD) in preparing students' global competencies through a literature review. The method used is a qualitative research approach with a literature study sourced from scientific journals, academic books, and relevant educational documents from 2020–2025. Data analysis was conducted using content analysis techniques through data reduction, grouping themes, and synthesis of findings. The results of the study indicate that elementary school age is the optimal phase for language acquisition, so that early English learning can improve students' communication skills, digital literacy, and cultural openness. Communicative and contextual learning has been proven effective in increasing student motivation and self-confidence. Despite challenges such as limited teacher competence and students' fear of speaking English, English learning in elementary schools remains a crucial investment in preparing a generation ready to face global demands.